ANALYSIS OF THE INFLUENCE OF JKN MOBILE USERS ON PERCEPTIONS OF PATIENT SATISFACTION OUTPATIENT CARE AT YAPIKA HOSPITAL: ANALISIS PENGARUH PENGGUNAAN JKN MOBILE TERHADAP PERSEPSI KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT YAPIKA - Nuraisyah Zabrina Adzhara; Rusmin, Muhammad; Lagu, Abd. Majid H. R; Syarfaini (Homes Journal = Hospital Management Studies Journal, 2026)
Background: This study aims to examine the relationship between the use of Mobile JKN and outpatient satisfaction at Yapika General Hospital, using five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Objective: The purpose of this study is to examine the relationship between the use of Mobile JKN digital services and outpatient satisfaction at Yapika General Hospital. Methods: This study employed a quantitative design with a cross-sectional approach. The sample size was 150 respondents, determined through accidental sampling. Data were collected using a Likert-based questionnaire and analyzed through univariate and bivariate tests with a significance level of α = 0.05.  Results: Based on statistical tests, the variables reliability, responsiveness, and assurance significantly influenced patient satisfaction (p<0.05). Meanwhile, the dimensions tangible evidence and empathy did not show a statistically significant relationship (p>0.05). Conclusion: Utilization of the Mobile JKN application has generally met patient satisfaction, but strengthening the empathy aspect is needed to improve overall service quality.